1999
DOI: 10.4049/jimmunol.162.6.3639
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Promote Nonphlogistic Phagocytosis of Apoptotic Leukocytes

Abstract: Phagocyte recognition, uptake, and nonphlogistic degradation of neutrophils and other leukocytes undergoing apoptosis promote the resolution of inflammation. This study assessed the effects of anti-inflammatory glucocorticoids on this leukocyte clearance mechanism. Pretreatment of “semimature” 5-day human monocyte-derived macrophages (Mφ) for 24 h with methylprednisolone, dexamethasone, and hydrocortisone, but not the nonglucocorticoid steroids aldosterone, estradiol, and progesterone, potentiated phagocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Efferocytosis describes the ability of a macrophage to clear apoptotic cells. The ability of glucocorticoids to upregulate AM efferocytosis is dependent on HSD-1 expression ( 17 , 18 ). Glucocorticoids increase macrophage efferocytosis partly by upregulating expression of the efferocytosis receptor Mer ( 37 , 38 ) and downregulating expression of the inhibitory receptor Signal Regulatory Protein-α (SIRPα) ( 39 ) on the surface of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efferocytosis describes the ability of a macrophage to clear apoptotic cells. The ability of glucocorticoids to upregulate AM efferocytosis is dependent on HSD-1 expression ( 17 , 18 ). Glucocorticoids increase macrophage efferocytosis partly by upregulating expression of the efferocytosis receptor Mer ( 37 , 38 ) and downregulating expression of the inhibitory receptor Signal Regulatory Protein-α (SIRPα) ( 39 ) on the surface of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Efferocytosis is a process associated with the suppression of inflammatory responses and promotion of tissue repair ( 15 , 16 ). Glucocorticoids have the ability to upregulate macrophage efferocytosis; but this capacity is dependent on HSD-1 expression ( 17 , 18 ). Murine studies have shown that macrophage HSD-1 deficiency is associated with impaired efferocytosis of apoptotic neutrophils in a model of peritonitis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…31,34 Although systemic steroids are commonly used, the level of evidence for their use is low and inconsistent. 5,28,31 Glucocorticoids have pro-resolution inflammatory properties thus attenuate the acute inflammatory process 35 through the various cellular and chemical mechanisms including the down-regulation of cytokine gene expression such as of TNF-α 36 and promotion of nonphlogistic phagocytosis of apoptotic leucocytes. 35 A few case series have shown benefit with reduction in morbidity when treated with systemic steroids 37,38 whereas others have reported increased morbidity with longer healing time.…”
Section: Discussionmentioning
confidence: 99%
“…5,28,31 Glucocorticoids have pro-resolution inflammatory properties thus attenuate the acute inflammatory process 35 through the various cellular and chemical mechanisms including the down-regulation of cytokine gene expression such as of TNF-α 36 and promotion of nonphlogistic phagocytosis of apoptotic leucocytes. 35 A few case series have shown benefit with reduction in morbidity when treated with systemic steroids 37,38 whereas others have reported increased morbidity with longer healing time. 39 Baillis and Maize 7 reported a case with successful use of adalimumab, a recombinant IgG1 monoclonal antibody with specificity for human TNF-α in the treatment of recalcitrant EM.…”
Section: Discussionmentioning
confidence: 99%
“…Various efferocytosis receptor combinations are produced by phagocytes, in different organs, but they all come and work together at the phagocytic synapse to mediate tethering and generate enough engulfment signals after macrophages connect to the apoptotic cells 9 . Previously, the glucocorticoid receptor (GR) and retinoic acid receptors (RARs) nuclear receptors were shown to increase efferocytosis in macrophages by promoting the transcription of key phagocytic machinery genes 10 12 .…”
Section: Introductionmentioning
confidence: 99%